Clinical implications of admission anemia for electroconvulsive therapy planning in adolescent major depressive disorder: identifying vulnerable subgroups with poorer response - Geng, Dandan; Xu, Heyan; Gou, Jijia; Wang, Yuna; Chen, Yujia; Hong, Su; Kuang, Li (Frontiers in Psychiatry, 2026)
BackgroundMajor depressive disorder (MDD) represents a grave worldwide concern, particularly afflicting the adolescent population. Electroconvulsive therapy (ECT) is widely regarded as a gold-standard intervention for severe forms of MDD, although treatment response varies considerably among individuals. Growing evidence suggests that hematological parameters may influence therapeutic outcomes. This study sought to examine the link between admission anemia and response to ECT treatment.MethodsWe analyzed 381 adolescent MDD patients who underwent ECT, comparing demographic and hematological indicators between responders and non-responders. Subgroup analyses were conducted based on gender and depressive subtypes.ResultsAmong the 381 patients treated with ECT, 272 (71.4%) were classified as responders. Non-responders showed significantly lower baseline hemoglobin levels compared to responders (mean ± SD: 119.0 ± 9.7 vs. 128.7 ± 13.1, p < 0.001). Analysis identified a significant link between hemoglobin levels at admission and the percentage improvement on the HAMD-17 (r = 0.231, p < 0.001). Following confounder adjustment in a binary logistic regression model, anemia at admission was correlated with a lower probability of ECT response [OR (95% CI): 4.051 (2.399-6.840), p < 0.001]. Females and patients with psychotic depression were particularly more susceptible to the impact of admission anemia.ConclusionAdmission anemia is associated with poorer ECT efficacy in adolescent MDD patients. Assessing baseline hemoglobin levels may help optimize ECT treatment planning, especially in female patients and those with psychotic depression.